Engineered spermidine-secreting Saccharomyces boulardii enhances olfactory memory in Drosophila melanogaster - Parweez, Florance; Palou, Roger; Li, Ruizhen; Kadhim, Lanna; MacMillan, Heath; Tyers, Mike; Liu, X. Johné (Frontiers in Neuroscience, 2025)
IntroductionThe polyamines putrescine, spermidine, and spermine are ubiquitous metabolites synthesized in all cells. The intracellular levels of polyamines, especially spermidine, decrease in aging. Oral spermidine supplementation has been reported to alleviate aspects of aging-related disease in animal models, including decline in learning and memory. The diverse health benefits of spermidine supplementation, often at doses that do not significantly alter spermidine levels of target organs, suggests that exogenous spermidine may have a common site of action, the gastrointestinal (GI) tract.MethodsTo directly deliver spermidine to the GI tract with minimum impact on the global spermidine levels, we engineered the probiotic yeast Sacchromyces boulardii (Sb) to overproduce and secrete spermidine. We tested the effects of a spermidine-producing yeast strain (Sb576) on aging-associated learning and memory decline in an olfactory classical conditioning assay in Drosophila melanogaster.ResultsFeeding of newly eclosed flies of the wild-type (w1118) strain for 30 days with food supplemented with live Sb576, but not live wild-type Sb (SbWT) or free spermidine, reduced aging-associated short-term memory (STM) decline. Notably, Sb576 supplementation, but not SbWT or spermidine supplementation, of either young flies or old flies for only three days also enhanced STM without affecting locomotive ability. Furthermore, we showed that Sb576 supplementation also significantly reduced aging-associated STM decline in Dh31R, a mutant strain lacking the diuretic hormone 31 receptor, which exhibits compromised learning and memory.ConclusionThese results demonstrate that in situ production of spermidine by a synthetic biotic yeast in the GI tract can enhance STM and further suggest a mechanism involving the gut-brain axis.